STONEHENGE — Suite for nonlinear analysis of energy harvesting systems[Formula presented] - Norenberg, João Pedro [UNESP]; Peterson, João Victor; Lopes, Vinicius Gonçalves; Luo, Roberto; de la Roca, Leonardo; Pereira, Marcelo; Telles Ribeiro, José Geraldo; Cunha, Americo (Elsevier, 2021)
STONEHENGE is a toolbox designed to evaluate nonlinear vibration-based energy harvesting systems, which demand careful studies regarding their nontrivial behavior. It is composed of an ensemble of codes to study and characterize the dynamic behavior, as well as deal with varieties of physical parameters and excitation. For this, it has six modules, initial value problem, dynamic animation, nonlinear tools, sensitivity analysis, stochastic simulation, and chaos control. A bistable oscillator is used as a benchmark for a vibration harvester. We hope this toolbox can contribute to the development and improvement of old and new generations of nonlinear vibration-based energy harvesting systems.
Keywords: Basins of attraction; Bifurcation diagram; Chaos control; Energy harvesting; Nonlinear dynamics; Sensitivity analysis; Stochastic simulation